FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) PADA WANITA USIA 15-49 TAHUN DI WILAYAH PEDESAAN DI INDONESIA (ANALISIS DATA SDKI 2017) - Putri, Naura Athira; Ronoatmodjo, Sudarto (Jurnal Kesehatan Masyarakat, 2023)
The Long-Term Contraceptive Method (LTCM) is a contraceptive method that can be used for a long time, start from 3 years to permanent. Contraceptive method that are included in LTCM are IUD, implant, tubectomy, and vasectomy. According to the 2017 IDHS data, LTCM utilization prevalence is much lower in number, compared to the Short-Term Contraceptive Method utilization, even though LTCM is more efficient and safe way to prevent pregnancy. The most used contraceptive method is injectables (29%) and pills (12%) Meanwhile, there are only 5% use IUD, 5% use Implant, 4% use tubectomy, and <1% use vasectomy. This study’s objective is to describe the prevalence of LTCM utilization in Indonesia’s rural areas, describe the individual characteristics in Indonesia’s rural areas, and determine the associated factors of LTCM utilization in women aged 15-49 in Indonesia’s rural areas. This is a cross-sectional study using secondary data from IDHS 2017. The analysis used in this study is Chi-Square test and Cox Regression test. The results found that there are significant association between age (APR = 1,4; 95% CI = 1,28-1,56), education level (APR = 1,3; 95% CI = 1,18-1,44), economic status (APR=1,2; 95% CI=1,05-1,33), parity (APR = 1,4; 95% CI = 1,24-1,51), knowledge of contraception (APR = 1,5; 95% CI = 1,32-1,59), source of contraception service (APR = 2; 95% CI = 1,80-2,20), family planning information exposure (APR = 1,1; 95% CI = 1,00-1,21), and partner support to the utilization of LTCM (APR = 1,7; 95% CI = 1,13-2,68). Source of contraception service is the predominant factor in this study (APR = 2; 95% CI = 1,80-2,20).